Technoeconomic and Carbon Emission Analysis for a Grid-Connected Photovoltaic System in Malacca. (1st July 2012) - Teoh, Wei Yee; Khu, Say Yen; Tan, Chee Wei; Hii, Ing Hui; Cheu, Kai Wee
Abstract : A 1 MW grid-connected PV system is studied and analyzed in this project using the National Renewable Energy Laboratory's HOMER simulation software. The economic feasibility of the system in a small industry area of Malacca, Rembia in Malaysia, is investigated. The aim of the proposed PV system is to reduce the grid energy consumption and promote the use of renewable energy. In this paper, the emphasis is placed on the reduction of greenhouse gases emission. HOMER is capable of performing simulation on renewable energy systems as well as system optimization, in which, the optimization is based on the available usage data and the renewable energy data, such as solar irradiance and temperature. In addition, HOMER can perform sensitivity analysis according to different assumptions of uncertainty factors to determine its impact on the studied system and also the per unit energy cost. Finally, the most suitable or the best configuration system can be identified based on the requirements and constraints.